Report of Committee on Confederate Relations, prescribing the time for which volunteers are to be mustered into service (LLMC-digital (Series), 1861)
Contains the 1861 report from the Committee on Confederate Relations, which communicated a letter from the Secretary of War, regarding the time for which volunteers are to be mustered into service. The committee concluded that the service should be for twelve months.